Strategi Pemasaran Digital Melalui Marketplace Facebook Pada Jati Subur Mobil - M Wisnu Dwimahatma; Muhammad Bhirawa Dwi Atma Citalada (LPPI UMN AL WASHLIYAH, 2025)
The advancement of digital technology has led to significant changes in marketing, including in the used car sales sector. This journal aims to explore digital marketing strategies through Facebook Marketplace by the Jati Subur Mobil showroom. Based on the findings, Facebook Marketplace has proven effective in expanding marketing reach and increasing the chances of products being seen by potential buyers. However, there are also several challenges encountered, such as numerous responses from non-serious users and high competition among businesses. By implementing strategies such as using attractive images, informative advertisement titles, quick responses, and complete descriptions, the showroom has succeeded in enhancing its sales potential.